THE FRENCH PARADOX: HOW CAN WE EXPLAIN THE ASSIMILATION OF HEALTH BIOTECHNOGIES? - Xavier PARISOT; Bertrand PAUGET (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice, 2013)
There is in France and more generally in Europe a paradox. In the agro industry business, the use of biotechnology is suspicious and controversy (see for example the emblematic case of GMOs), the subject is little debate in the health sector. Yet, in those two sectors, the production process of biotechnology is the same. How can we explain those differences? This article aims to explain the reasons for the acceptance of biotechnology in the business of health. Health professionals interviewed in this study leave use the biotechnology as a tool to improve their practices and benefiting their patients. In doing so, they play a key role to facilitate their consumption by the public. This article is based on a qualitative and exploratory methodology. Our sample consists of leaders of biotech companies or selling biotechnology and doctors who use them.